How we get free eaudiobook Black feminism and the combahee river collective. - Taylor, Keeanga-Yamahtta (Tantor Media, 2018)
The Combahee River Collective, a path-breaking group of radical black feminists, was one of the most important organizations to develop out of the antiracist and women's liberation movements of the 1960s and 70s. In this collection of essays and interviews edited by activist-scholar Keeanga-Yamahtta Taylor, founding members of the organization and contemporary activists reflect on the legacy of its contributions to black feminism and its impact on today's struggles.